Long‐term cumulative incidence of cervical intraepithelial neoplasia grade 3 or worse after abnormal cytology: Impact of HIV infection. Issue 8 (29th October 2013) - Massad, L. Stewart; Pierce, Christopher B.; Minkoff, Howard; Watts, D. Heather; Darragh, Teresa M.; Sanchez‐Keeland, Lorraine; Wright, Rodney L.; Colie, Christine; D'Souza, Gypsyamber
<x xml:space="preserve">Abstract</x> To estimate the long term cumulative risk for cervical intraepithelial neoplasia grade 3 or worse after an abnormal cervical Pap test and to assess the effect of HIV infection on that risk. Participants in the Women's Interagency HIV Study were followed semiannually for up to 10 years. Pap tests were categorized according to the 1991 Bethesda system. Colposcopy was prescribed within 6 months of any abnormality. Risk for biopsy‐confirmed CIN3 or worse after abnormal cytology and at least 12 months follow‐up was assessed using Kaplan–Meier curves and compared using log‐rank tests. Risk for CIN2 or worse was also assessed, since CIN2 is the threshold for treatment. After a median of 3 years of observation, 1, 947 (85%) women subsequently presented for colposcopy (1, 571 [81%] HIV seropositive, 376 [19%] seronegative). CIN2 or worse was found in 329 (21%) of HIV seropositive and 42 (11%) seronegative women. CIN3 or worse was found in 141 (9%) of seropositive and 22 (6%) seronegative women. In multivariable analysis, after controlling for cytology grade HIV seropositive women had an increased risk for CIN2 or worse (H.R. 1.66, 95% C.I 1.15, 2.45) but higher risk for CIN3 or worse did not reach significance (H.R. 1.33, 95% C.I. 0.79, 2.34). HIV seropositive women with abnormal Paps face a marginally increased and long‐term risk for cervical disease compared to HIV seronegative women, but most women with ASCUS and LSIL Pap results do not develop CIN2 or worse despite years of observation.